Avaliação da massa muscular do quadríceps femoral, por meio da ultrassonografia, em pacientes com doença pulmonar obstrutiva crônica - Barros, Elizeu Alves (2024)
The quadriceps is an expressive muscle group in the human body and therefore, when affected by a great loss of muscle mass, it can compromise the functionality and quality of life of individuals with Chronic Obstructive Pulmonary Disease (COPD). Therefore, evaluation methods in this patient profile are important to help control and follow-up due to the treatment. For example, the literature mentions ultrasound as a viable, reliable and reproducible tool for this purpose.Objective:To analyze the feasibility of the Sonographic thigh index, in the assessment of muscle mass deficit and its correlation with the cross-sectional area of the rectus femoris (ASTRF) and quadriceps muscle thickness (QME) in individuals with COPD and compared to a group control. Method: This is a cross-sectional study, carried out at Outpatient Clinic II of the Hospital Universitário Júlio Muller (HUJM). The study evaluated 27 patients of both sexes divided into two groups: COPD Group (n= 13 individuals) and Control Group (n= 14 individuals), from August 2022 to February 2023. The following evaluations were performed: spirometry (FEV1; FVC; FEV1/FVC ratio); CAT questionnaire (CPOD Assessment Test); mMRC scale (modified Medical Research Council scale); perimetry of the dominant lower limb; (ASTRF) analysis; (EMQ) and the SSI by calculation (EMQ/BMI), both using ultrasound. Results: Mean and standard deviation values for the age of the participants corresponded to 62.0 ± 10.9 years and the body mass index was 27.23 ± 5.8 kg/m2. In the COPD group, the means of ASTRF, EMQ in the COPD group were respectively (4.3 ± 1.8 cm2; 2.4 ± 1.1 cm). The ISC was 1.0 ± 0.3 for men and 0.8 ± 0.2 for women, in the control group the ASTRF and EMQ values were 5.4 ± 1.6 cm2; 2.9±0.6 cm, respectively; and the ISC values corresponded to 0.9 ± 0.1 for men and 0.9 ±0.2 for women. The SSI showed a strong correlation and statistical significance with the EMQ in both groups: COPD group: r=0.778, p= 0.001 vs. Control group: r=0.796, p>0.001. Person's correlation showed an excellent relationship between physician and researcher in the analysis of the ASTRF (r= 0.97, 95%CI 0.94-0.99) and in relation to the EMQ (r= 0.94, 95%CI 0.89- 0.98). Conclusion: The SSI calculation is a parameter for independent and reproducible loss of muscle mass with good correlation with EMQ. New studies need to be carried out in order to define a quantitative parameter of quadriceps femoris muscle loss based on ultrasound in individuals with DPOC.